Irrational career beliefs in agricultural education students, demographics, impacts, and rational career education intervention. - Ifeanyieze, Florence Obiageli; Ede, Moses Onyemaechi; Ejiofor, Tochukwu E.; Ekenta, Lilian Ukamaka; Onah, Ogechukwu; Okechukwu, Favour C.; Isiwu, Edward Chukwuka; Ogbonna, Emeka; Azunku, Francis; Nwankwo, Clara Ukamaka; Ezebuiro, Felicia; Onah, Fredrick Chinedu; et al. (Medicine, 2021)
Background: Studies have shown that a good number of students admitted into Agricultural Science Education program in Nigerian universities exhibit irrational career interest which affects their perceptions, feelings, and academic behaviors. This study, therefore, explored the effect of rational emotive career education on irrational career beliefs among students enrolled in agricultural education program in federal universities in Enugu state. Three null hypotheses guided the study.Method: Of the population (N = 79 students) targeted for the study and who underwent a screening exercise, 61 students were recruited as participants/sample size for the study. Sequence allocation software was used to assign 31 students into experimental groups and 30 into waitlisted control group. Participants in the intervention group received a rational emotive career education program that lasted for 12 sessions while those in waitlisted group did not receive the intervention. The participants in both groups were assessed at three points (Time 1, Time 2, and Time 3) using rational and irrational belief scale. A repeated measure (ANOVA) and partial eta square statistical tools were used to analyze the data collected.Result: This study result showed that rational emotive career education significantly reduced irrational career beliefs among students enrolled in Agricultural Science Education program exposed to intervention group compared to those in waitlisted control group. It also showed that there was time × group interaction for irrational career beliefs. The follow-up assessment indicated that the efficacy of rational emotive career education was sustained overtime.Conclusion: This study concluded that rational emotive career education is beneficial in reducing irrational career beliefs of university students enrolled in Agricultural Science Education program. Recommendations were also made in line with the results.